Pengembangan Media Pembelajaran Interaktif Berbentuk Video Animasi Berbantuan Aplikasi Filmora Pada Pembelajaran Pecahan Siswa Kelas V Sekolah Dasar - Ditha Tiara; Sutarini (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This study aims to analyze student responses, validity and effectiveness of the development of interactive learning media in the form of animated videos assisted by Filmora application in learning fractions of grade V elementary school students. This research uses the learning device development model suggested by S.Thiagarajan, namely the 4d model (Define, Design, Develop and Disseminate). The instruments used in this research are validation questionnaire, needs and test sheets. From the results of student responses, it is known that students really like and are interested in interactive learning media in the form of animated videos aided by the Filmora application that researchers develop, it can be seen from the student response which shows an average of 83.5% with the criteria "very good. Furthermore, the validity and effectiveness of the product were carried out, involving learning practitioners, material experts, interactive media and students to conduct pretests and posttests. The result of the validity is that the media is very valid with a validity percentage of 87.6% and a category of "very valid" and only requires minor revisions. Finally, the effectiveness test was conducted to determine the effectiveness of the product developed by conducting pretests and postests, and the result was that interactive learning media in the form of animated videos assisted by the Filmora application in learning fractions of grade V elementary school students were effective in improving student learning outcomes, it was seen from the increase in student scores before and after using interactive learning media.